EXPERIMENTAL RESEARCH PSYCHOLOGICAL AND PSYCHOPHYSIOLOGICAL OF CHARACTERISTICS DRIVERS - O. V. Pavlovskaya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The question of the measures to ensure a trouble-free road management is currently controversial and requires a systematic approach. However, there is no doubt the fact that trouble-free car driving is associated with certain psychophysiological qualities of the driver. At the moment, an urgent task is integral assessment of psychological and psycho-physiological characteristics that affect the reliability of the professional activities of motor vehicle drivers.